Technical perspectives on knowledge management system in bioinformatics environment - Hairudin, Nurul Haslina; Abdullah, Rusli; Atan, Rodziah; Ibrahim, Hamidah; Napis, Suhaimi; Hamidon @ Md Jamil, Siti Hernazura (Universiti Utara Malaysia, 2008)
The knowledge growth in the Bioinformatics environment needs a system that can organize and manage the biological knowledge. Knowledge Management System is appropriately for acquiring, storing, applying and disseminating that biological knowledge. In order to develop the system, the technical perspectives of Knowledge Management should take into account. In this paper, we discuss the technical perspectives of Knowledge Management System and the suitable method and technologies to be implemented in the system.